In vitro antifungal/fungistatic activity of manganese phosphite against soybean soil-borne pathogens - Carmona, Marcelo Anibal; Simonetti, Ester; Ravotti, Maximiliano Ezequiel; Scandiani, María Mercedes; Luque, A.G.; Formento, Angela Norma; Sautua, Francisco José (Fundación Rómulo Raggio, 2024)
Soybean root and stem rots caused by soil-borne pathogens are diseases commonly found in soybean fields, and one of the most important causes of crop losses. In the present study, the mycelial sensitivity of Fusarium virguliforme, F. tucumaniae, Sclerotinia sclerotiorum and Macrophomina phaseolina was evaluated on potato dextrose agar media (25 mL) supplemented with different concentrations of manganese phosphite (MnPhi) diluted in water (0, 25, 37.5, 50, 100, 200, 300, 400, 500, 800 and 1000 μg/mL). Mycelial growth sensitivity was analyzed using logarithmic linear regression analysis. The MnPhi concentration needed to inhibit 50% of the mycelial growth (IC50) ranged from 105 μg/mL (Fusarium spp.) to 409 μg/mL (M. phaseolina). Sclerotia were completely inhibited at 500 μg/mL. The results of our study represent the first report on the direct in vitro fungicidal/fungistatic action of MnPhi against fungi that are causal agents of soil-borne diseases.